method for production of activated carbon materials "Borysfen" using periodic carbonization of cellulosic fibrous materials - FERLIKOVSKYI VIKTOR IVANOVYCH; VOLFMAN VOLODYMYR ILLICH; SHOLOMYTSKYI LEONID VALENTYNOVYCH; TRYZNA ANATOLII ANDRIIOVYCH; KUDRIACHENKO VIKTOR VOLODYMYROVYCH; KOLOSOV OLEKSANDR YEVHENOVYCH (2010)
A method for production of activated carbon materials "Borysfen" using periodic carbonization of cellulosic fibrous materials, which includes pre-treatment of fibres by organic-silicon compounds, carbonization of the fibres at the temperature of 200 to 350 °C up to obtaining the mass loss from initial fibre weight measured in %, in a given range, further activation of the carbonized fibre in an oven or activation chamber in the temperature range, high value of which does not exceed 1000 °C, in an atmosphere containing a predetermined minimum amount of steam, which is formed as a result of water supply to the furnace to achieve the degree of burning of activated cellulose fibres measured in % within pre-defined limits, the novelty is that fibrous cellulosic material subject to activation is placed without tension on trays made in the form of a framework and is arranged layer-by-layer in parallel to the furnace base in the retort made in the form of a metal container without a lid with a shape similar to the inner surface of activation chamber, between cellulose material subject to activation and the basis of tray a damping material is located without contact with cellulose material subject to activation, from the side of retort base an adjustable flow of steam of uniform concentration in the range of 24-36 l/h of water per 1 kg of initial cellulosic material is provided throughout the entire volume of the retort or furnace, the porosity of the activated cellulosic material is determined, and as a result of activation fibrous activated carbon material is obtained, which is characterized by the value of benzene sorption capacity in the range of 1.2 to 2 cm/g at a value of the degree of burning activated polymer fibres ranging from 50 to 70 %. У способі одержання активованих вуглецевих матеріалів марки "Борисфен" з використанням періодичної карбонізації целюлозних волокнистих матеріалів, що включає попередню обробку волокон кремнійорганічними сполуками, карбонізацію волокон при температурі від 200 до 350 °С до одержання втрати маси від початкової маси волокна, вимірюваної в %, у заданому діапазоні, подальше активування карбонізованого волокна в печі або камері активування в температурному діапазоні, верхнє значення якого не перевищує 1000 °С, в атмосфері, що містить наперед задану мінімальну кількість пари, яка утворюється в результаті подачі води в піч, до досягнення ступеня обгару активованих целюлозних волокон, вимірюваного у %, в наперед заданих межах, новим є те, що волокнистий целюлозний матеріал, що активують, розміщують без натягнення на піддони, які виконані у вигляді каркаса і пошарово розташовують паралельно основі печі у реторті, що виконана у вигляді металевої ємності без кришки з формою, подібною внутрішній поверхні камери активування, між целюлозним матеріалом, що активують, і основою піддона розміщують демпфувальний матеріал без контакту з целюлозним матеріалом, що активують, з боку основи реторти забезпечують регульовану по витраті в діапазоні 24-36 л/води на годину на початкового целюлозного матеріалу подачу пари рівномірної концентрації по усьому об'єму реторти або печі, визначають пористість активованого целюлозного матеріалу, а в результаті активації одержують волокнистий активований вуглецевий матеріал, який характеризується значенням сорбційної ємкості по бензолу в межах від 1,2 до 2,4 см/г при значенні ступеня обгару актив